Dampak Bullying Terhadap Perilaku Remaja (Studi pada SMKN 5 Mataram) - Mintasri hardi; Abdul Kharis; Nur' aini (Universitas Muhammadiyah Mataram, 2019)
This research was conducted due to the spread of bullying phenomenon among adolescents. This research aims to find how the impact of bullying on adolescent behaviour. and how schools overcome the impact of bullying in the school environment. This research type was descriptive qualitative research. The informants of the study consisted of 35 students, 2 homeroom teachers, and 2 counselor teachers of SMKN 5 Mataram. Data collection methods used are observation, interviews, and documentation. Analysis of data used is to data reduction, data display, and data conclusions and verification. To measure the validity of the data of this study using resource triangulation. The results showed that the impact of bullying on the behavior of victims caused victims to fear and withdraw from the social environment, just let it go, and made bullying as a driver to be better than before, also students who became victims against the students who bullied him is the emergence of feelings of guilt and regret in the offender. The way schools to overcome the effects of bullying in the school environment is by giving suggestions and motivation to the perpetrators and victims of bullying.